Mechanisms of Action of Plant Extracts as Alternatives to Antibiotics in Aquaculture: A Comprehensive Review of Recent Studies - Mohamed Omar Abdalla Salem, (Al-imad Journal of Humanities and Applied Sciences (AJHAS), 2026)
The overuse of antibiotics in aquaculture has led to the emergence of antimicrobial resistance, environmental contamination, and concerns regarding food safety, necessitating the search for effective and eco-friendly alternatives. Plant-derived bioactive compounds, collectively known as phytobiotics, have gained considerable attention as promising substitutes due to their multifaceted biological activities. This comprehensive review synthesizes recent findings on the mechanisms of action through which plant extracts exert their beneficial effects in farmed fish species. The major mechanisms identified include direct antimicrobial activity through disruption of bacterial cell walls and inhibition of quorum sensing, immunomodulation via enhancement of both nonspecific and specific immune parameters, antioxidant protection through upregulation of endogenous enzyme systems, and growth promotion mediated by improved digestive enzyme activity and nutrient utilization. The review systematically examines how different classes of phytochemicals—including alkaloids, flavonoids, essential oils, phenolics, saponins, and polysaccharides—contribute to these effects. Evidence from recent studies demonstrates that plant extracts enhance lysozyme activity, phagocytosis, respiratory burst, and immune-related gene expression while reducing oxidative stress markers and improving resistance against major bacterial pathogens such as Aeromonas hydrophila, Vibrio species, and Yersinia ruckeri. Factors influencing phytobiotic efficacy, including extraction methods, dosage optimization, and advanced delivery systems like microencapsulation, are critically evaluated. The review also identifies current research gaps and proposes future directions, emphasizing the need for standardized protocols, omics-based mechanistic studies, and commercially scalable formulations to facilitate the transition from experimental findings to practical aquaculture applications. By consolidating current knowledge on mechanisms of action, this review contributes to the strategic adoption of plant extracts as sustainable alternatives to antibiotics in aquaculture.
Keywords: Phytobiotics; plant extracts; aquaculture; immunostimulation; antimicrobial activity; antioxidant mechanisms; antibiotic alternatives; bioactive compounds; fish health; sustainable aquaculture